مراسيل مصنف ابن أبي شيبة في كتاب الأيمان والنذور والكفارة دراسة تخريجية تحليلية - Rauf, Rusmin Abdul (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2020)
This research addresses the Mursal Hadith in the Musannaf (compilation) of Ibn Abi Shaybah, by collection them from the Book of Oath, Vow, Atonement. They are studied in term of matn (their text) and sanad (chain of narration). A brief introduction of the narrator of the musannaf is also given. Attestation of the hadith in other books is examined and the status of hadith is determined, whether they remain daif (weak) or upgraded to be hasan li gharihi. This is concluded with some available jurisprudence. The researcher used the inductive method to collect mursal hadith in the Musannaf of Ibn Abi Shaybah from the Book of Oath, Vow, Atonement and used the critical approach on the attestation in other books and determine the status of the hadith and used the analytical method to conclude on some jurisprudence of the Mursal Hadith. As a result, the researcher found most of mursal hadith in the musannaf eligible to be upgraded into hasan li gharihi. And the rest remain daif due the unavailable attestation in another book or weaken narrator.